Clinical features and comorbidity pattern of HCV infected migrants compared to native patients in care in Italy: A real-life evaluation of the PITER cohort. Issue 12 (December 2021) - Quaranta, Maria Giovanna; Ferrigno, Luigina; Tata, Xhimi; D'Angelo, Franca; Massari, Marco; Coppola, Carmine; Biliotti, Elisa; Giorgini, Alessia; Laccabue, Diletta; Ciancio, Alessia; Blanc, Pier Luigi; Margotti, Marzia; et al.
Abstract: Background: Direct-acting antivirals are highly effective for the treatment of hepatitis C virus (HCV) infection, regardless race/ethnicity. We aimed to evaluate demographic, virological and clinical data of HCV-infected migrants vs. natives consecutively enrolled in the PITER cohort. Methods: Migrants were defined by country of birth and nationality that was different from Italy. Mann-Whitney U test, Chi-squared test and multiple logistic regression were used. Results: Of 10, 669 enrolled patients, 301 (2.8%) were migrants: median age 47 vs. 62 years, ( p  < 0.001), females 56.5% vs. 45.3%, ( p  < 0.001), HBsAg positivity 3.8% vs. 1.4%, ( p  < 0.05). Genotype 1b was prevalent in both groups, whereas genotype 4 was more prevalent in migrants ( p  < 0.05). Liver disease severity and sustained virologic response (SVR) were similar. A higher prevalence of comorbidities was reported for natives compared to migrants ( p  < 0.05). Liver disease progression cofactors (HBsAg, HIV coinfection, alcohol abuse, potential metabolic syndrome) were present in 39.1% and 47.1% ( p  > 0.05) of migrants and natives who eradicated HCV, respectively. Conclusion: Compared to natives, HCV-infected migrants in care have different demographics, HCV genotypes, viral coinfections and comorbidities and similar disease severity, SVR and cofactors for disease progression after HCV eradication. A periodic clinical assessment after HCV eradication in Italians and migrants with cofactors for disease progression is warranted.